A bioactive injectable bulking material; a potential therapeutic approach for stress urinary incontinence. (June 2019) - Vardar, E.; Vythilingam, G.; Pinnagoda, K.; Engelhardt, E.M.; Zambelli, P.Y.; Hubbell, J.A.; Lutolf, M.P.; Frey, P.; Larsson, H.M.
Abstract: Stress urinary incontinence (SUI) is a life changing condition, affecting 20 million women worldwide. In this study, we developed a bioactive, injectable bulking agent that consists of Permacol™ (Medtronic, Switzerland) and recombinant insulin like growth factor-1 conjugated fibrin micro-beads (fib_rIGF-1) for its bulk stability and capacity to induce muscle regeneration. Therefore, Permacol™ formulations were injected in the submucosal space of rabbit bladders. The ability of a bulking material to form a stable and muscle-inducing bulk represents for us a promising therapeutic approach to achieve a long-lasting treatment for SUI. The fib_rIGF-1 showed no adverse effect on human smooth muscle cell metabolic activity and viability in vitro based on AlamarBlue assays and Live/Dead staining. Three months after injection of fib_rIGF-1 together with Permacol™ into the rabbit bladder wall, we observed a smooth muscle tissue like formation within the injected materials. Positive staining for alpha smooth muscle actin, calponin, and caldesmon demonstrated a contractile phenotype of the newly formed smooth muscle tissue. Moreover, the fib_rIGF-1 treated group also improved the neovascularization at the injection site, confirmed by CD31 positive staining compared to bulks made of Permacol TM only. The results of this study encourage us to further develop this injectable, bioactive bulking material towards a future therapeutic approach for a minimal invasive and long-lasting treatment of SUI.